2024
DOI: 10.1080/15592324.2024.2331357
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interplay between melatonin and hydrogen sulfide enhances cadmium-induced oxidative stress resistance in stock ( Matthiola incana L.)

Faisal Zulfiqar,
Anam Moosa,
Hayssam M. Ali
et al.

Abstract: Ornamental crops particularly cut flowers are considered sensitive to heavy metals (HMs) induced oxidative stress condition. Melatonin (MLT) is a versatile phytohormone with the ability to mitigate abiotic stresses induced oxidative stress in plants. Similarly, signaling molecules such as hydrogen sulfide (H 2 S) have emerged as potential options for resolving HMs related problems in plants. The mechanisms underlying the combined application of MLT and H 2 S are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Ryegrass ( Lolium perenne L.) is an important grass plant with multiple functions and applications, especially in ecological restoration [ 5 , 6 ]. Li et al [ 7 ] reported that Bacillus subtilis could adsorb Cd and improve Cd tolerance in Poa annua L. and alfalfa ( Medicago sativa L.).…”
Section: Introductionmentioning
confidence: 99%
“…Ryegrass ( Lolium perenne L.) is an important grass plant with multiple functions and applications, especially in ecological restoration [ 5 , 6 ]. Li et al [ 7 ] reported that Bacillus subtilis could adsorb Cd and improve Cd tolerance in Poa annua L. and alfalfa ( Medicago sativa L.).…”
Section: Introductionmentioning
confidence: 99%